2013
DOI: 10.1088/2041-8205/780/2/l20
|View full text |Cite
|
Sign up to set email alerts
|

NGC 1277: A Massive Compact Relic Galaxy in the Nearby Universe

Abstract: As early as 10 Gyr ago, galaxies with more than 10 11 M ⊙ in stars already existed. While most of these massive galaxies must have subsequently transformed through on-going star formation and mergers with other galaxies, a small fraction ( 0.1%) may have survived untouched till today. Searches for such relic galaxies, useful windows to explore the early Universe, have been inconclusive to date: galaxies with masses and sizes like those observed at high redshift (M ⋆ 10 11 M ⊙ ; R e 1.5 kpc) have been found in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
151
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(175 citation statements)
references
References 33 publications
18
151
0
Order By: Relevance
“…Compact candidates also present lower axis ratios than normal galaxies. These elongated shapes are common in massive compact galaxies, both at high-z (van der Wel et al 2011;Buitrago et al 2013), and at lower redshifts (Trujillo et al , 2014.…”
Section: The Final Samplementioning
confidence: 93%
See 2 more Smart Citations
“…Compact candidates also present lower axis ratios than normal galaxies. These elongated shapes are common in massive compact galaxies, both at high-z (van der Wel et al 2011;Buitrago et al 2013), and at lower redshifts (Trujillo et al , 2014.…”
Section: The Final Samplementioning
confidence: 93%
“…The yellow line with lighter yellow region plot abundances for compacts in the COSMOS area (Damjanov et al 2015a Taylor et al (2010) are shown here as upper limits (see red and cyan points with arrows). The blue triangle is for the lower limit at z ∼ 0 provided by Trujillo et al (2014). Orange and red lines plot abundances of relic galaxies from semi-analytical models (SAMs), based on Millennium N-body simulations (Quilis & Trujillo 2013).…”
Section: Abundance Vs Redshiftmentioning
confidence: 99%
See 1 more Smart Citation
“…The compact lenticular galaxy, NGC 1277, was found by van den Bosch et al (2012) to have an over-massive black hole of 1.7 × 10 10 M , which corresponds to 14 percent of the total stellar mass of that galaxy. The fraction is much larger than the typical value (0.1 percent) found in a normal massive galaxy (e.g.…”
Section: An Over-massive Black Hole In Ngc 1277?mentioning
confidence: 99%
“…Recently, the early-type galaxy NGC 1277 in the Perseus cluster received much attention because, according to stellar kinematics observations, it most likely hides an over-massive black hole of ∼10 10 M (van den Bosch et al 2012;Yıldırım et al 2015). Galaxies with the most massive black holes are interesting on their own, because they may serve as probes for black hole formation models (Khan et al 2015, and references therein), may indicate capture of a runaway black hole (Shields & Bonning 2013), and may constrain black hole-galaxy co-evolution models (Croton et al 2006;Somerville et al 2008).…”
Section: Introductionmentioning
confidence: 99%